Developing an Excellent Educational Management Model Based on Recognition of Prior Learning (RPL) in Senior High Schools of South Tangerang City - Sutarman; Haji Awg Asbol bin Haji Mail (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This study aims to develop an excellent educational management model based on Recognition of Prior Learning (RPL) in senior high schools of South Tangerang City. RPL is an approach that recognizes students’ prior knowledge, skills, and experiences acquired through formal, non-formal, and informal learning. In the context of secondary education, the integration of RPL into educational management is essential to enhance learning quality, promote student-centered approaches, and support lifelong learning principles. This research employed a Research and Development (R&D) design, involving needs analysis, model design, expert validation, and limited field testing. The participants included school principals, teachers, and students from selected senior high schools in South Tangerang City. Data were collected through interviews, observations, document analysis, and questionnaires. The data were analyzed using qualitative descriptive techniques and supported by quantitative data from validation and trial results. The findings indicate that the developed model consists of key components, including strategic planning, RPL-based assessment and validation, adaptive curriculum management, teacher capacity building, and continuous monitoring and evaluation. The model demonstrates a high level of validity, practicality, and effectiveness in improving student learning outcomes, enhancing recognition of prior competencies, and increasing the flexibility of learning processes. In conclusion, the proposed RPL-based educational management model provides an innovative and effective framework for improving the quality of education in senior high schools. It also contributes to the development of an inclusive and adaptive education system that supports lifelong learning in the modern era.